Economic Transformations and National Security Risks Generated by Cryptocurrencies - Bătuşaru Cristina Maria; Sbârcea Ioana Raluca (Scientific Bulletin)
The proliferation of cryptocurrencies has brought significant changes in the global economic market while introducing new risks to national security. This paper explores the economic transformations driven by the rise of digital currencies, analyzing their impact on traditional financial systems, monetary policy, and international trade. While cryptocurrencies offer opportunities for innovation and economic growth, they also pose substantial challenges for regulators, particularly in addressing illicit activities such as money laundering, terrorism financing, and tax evasion. Furthermore, the decentralized nature of these digital assets presents unique vulnerabilities for national security, as they can be used to avoid financial controls and sanctions. This paper aims to provide a comprehensive analysis of the economic benefits and security risks associated with cryptocurrencies, emphasizing the need for coordinated regulatory frameworks. By examining the intersection of technological innovation, economic impact, and security concerns, this research contributes to the ongoing debate on how to handle the main challenges brought by the growth of cryptocurrencies in a globalized, digital economy.